Straightforward Approach for Preparing Durable Antibacterial ZnO Nanoparticle Coatings on Flexible Substrates - Andris Šutka; Linda Mežule; Viktorija Denisova; Jochen Meier-Haack; Akshay Kulkarni; Sanda Bitina; Krisjanis Smits; Svetlana Vihodceva (Molecules, 2022)
Flexible antibacterial materials have gained utmost importance in protection from the distribution of bacteria and viruses due to the exceptional variety of applications. Herein, we demonstrate a readily scalable and rapid single-step approach for producing durable ZnO nanoparticle antibacterial coating on flexible polymer substrates at room temperature. Substrates used are polystyrene, poly(ethylene-co-vinyl acetate) copolymer, poly(methyl methacrylate), polypropylene, high density polyethylene and a commercial acrylate type adhesive tape. The deposition was achieved by a spin-coating process using a slurry of ZnO nanoparticles in toluene. A stable modification layer was obtained when toluene was a solvent for the polymer substrates, namely polystyrene and poly(ethylene-co-vinyl acetate). These coatings show high antibacterial efficiency causing >5 log decrease in the viable counts of Gram-negative bacteria Escherichia. coli and Gram-positive bacteria Staphylococcus aureus in 120 min. Even after tapping these coated surfaces 500 times, the antibacterial properties remained unchanged, showing that the coating obtained by the presented method is very robust. In contrast to the above findings, the coatings are unstable when toluene is not a solvent for the substrate.